2020
DOI: 10.3390/ijerph17103476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Fat Percentage on Muscle Damage Induced by High-Intensity Eccentric Exercise

Abstract: This study aimed to investigate the impact of percent body fat (%BF) on muscle damage after high-intensity eccentric exercise. Thirty healthy male undergraduates (mean age: 22.0 ± 2 years, height: 176.9 ± 5 cm, weight: 75.8 ± 11.6 kg) participated in this study, and they were classified according to their %BF into a high %fat group (HFG, ≥20%, n = 15) and a low %fat group (LFG, ≤15%, n = 15). For eccentric exercise, two sets of 25 reps were performed on a modified preacher curl machine using the elbow flexor m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Participants were randomly assigned as cryotherapy (WBC, n = 26) and control (CON, n = 15). To assess the influence of differing ages and body fat contents, the WBC group was sub-divided into old (OLD, ≥45, mean ± SD age 58.1 ± 7.9 years, n = 10) and young (YNG, <40, mean ± SD age 29.2 ± 7.6 years, n = 13) [ 31 ], as well as high fat (HFAT, ≥20%, mean ± SD body fat 23.0 ± 2.9%, n = 10) and low fat (LFAT, ≤15%, mean ± SD 13.8 ± 1.4%, n = 8) groups [ 30 ]. Three WBC participants were aged 40–44 and 8 WBC participants had 15.5–19.5% body fat, which were not part of these sub-groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were randomly assigned as cryotherapy (WBC, n = 26) and control (CON, n = 15). To assess the influence of differing ages and body fat contents, the WBC group was sub-divided into old (OLD, ≥45, mean ± SD age 58.1 ± 7.9 years, n = 10) and young (YNG, <40, mean ± SD age 29.2 ± 7.6 years, n = 13) [ 31 ], as well as high fat (HFAT, ≥20%, mean ± SD body fat 23.0 ± 2.9%, n = 10) and low fat (LFAT, ≤15%, mean ± SD 13.8 ± 1.4%, n = 8) groups [ 30 ]. Three WBC participants were aged 40–44 and 8 WBC participants had 15.5–19.5% body fat, which were not part of these sub-groups.…”
Section: Methodsmentioning
confidence: 99%
“…Since downhill running is a whole-body exercise that stresses several physiological systems, it is of interest to determine if WBC could enhance recovery following this modality. Other commonly adopted damage protocols, such as isolated eccentric leg extensions [ 28 ] and arm curls [ 29 , 30 ] may be less sports specific, so any WBC-induced responses may be less applicable for general sports recovery. Despite the extensive literature on downhill running and WBC, no study has yet to assess the impact of WBC on recovery following a downhill running bout.…”
Section: Introductionmentioning
confidence: 99%
“…In their recent study that used an eccentric exercise protocol for the elbow flexor similar to the one used by Kim and So, 14 Yoon and Kim 15 reported that while BMI can be used to make a simple diagnosis of obesity, it does not accurately represent the amount of adipose tissues; thus, they examined the association between %BF and muscle injury. They divided 30 healthy male university students into a high %BF (≥20%) group and a low %BF (≤15%) group according to their %BF and instructed them to perform high-intensity eccentric exercise.…”
Section: Effect Of Obesity On Exercise-induced Muscle Injurymentioning
confidence: 99%
“…Several studies have reported that obesity can affect the markers associated with exercise-induced muscle injury. 14 , 15 , 31 - 33 Salvadori et al 32 performed an exercise test in 10 healthy subjects with a mean BMI of 22 kg/m 2 and 11 obese patients with a mean BMI of 41 kg/m 2 using a cycle ergometer and reported that the obese patients showed higher increases in CK levels than did the healthy subjects. Paschalis et al 33 divided 22 healthy women into a lean group (BMI, 18.5–24.9 kg/m 2 ; mean BMI, 21.2 kg/m 2 ) and an overweight group (BMI, 25.0–33.0 kg/m 2 ; mean BMI, 29.5 kg/m 2 ) and instructed them to perform eccentric exercise of the knee extensor using an isokinetic dynamometer.…”
Section: Effect Of Obesity On Exercise-induced Muscle Injurymentioning
confidence: 99%
See 1 more Smart Citation